Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

"Die Geschichte als Dichterin". Analogien in kleinen historischen Porträts von Stefan Zweig. - Öhlschläger, Claudia (Lektüren der Ähnlichkeit um 1900.)

How do attitudes and self-efficacy predict teachers‘ intentions to teach in inclusive classrooms? A cross-national comparison between Canada, Germany, Greece, Italy, and Switzerland. - Sahli Lozano, Caroline; Wüthrich, Sergej; Kullmann, Harry; Knickenberg, Margarita; Sharma, Umesh; Loreman, Tim; Romano, Alessandra; Avramidis, Elias; Woodcock, Stuart; Subban, Pearl

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

An early indicator for anomalous stock market performance - Fritz, Marlon; Gries, Thomas; Wiechers, Lukas (Quantitative Finance)
We propose an indicator for detecting anomalous stock market valuation in real time such that market participants receive timely signals so as to be able to take stabilizing action. Unlike existing approaches, our anomaly indicator introduces three methodological novelties. First, we use an endogenous, purely data-driven, nonparametric trend identification method to separate long-term market movements from more short-term ones. Second, we apply SETAR models that allow for asymmetric expansions and contractions around the long-term trend and find systematic stock price cycles. Third, we implement these findings in our indicator and conduct real-time market forecasts, which have so far been neglected in the literature. Applications of our indicator using monthly S&P 500 stock data from 1970 to the end of 2022 show that short-term anomalous market movements can be identified in real time up to one year ahead. We predict all major anomalies, including the 1987 Bubble and the initial phase of the Financial Crisis that began in 2007. In total, our anomaly indicator identifies more than 80% of all – even minor – anomalous episodes. Thus, smoothing market exaggerations through early signaling seems possible.
Keywords: General Economics; Econometrics and Finance; Finance

Association of dietary patterns with diabetes-related comorbidities varies among diabetes endotypes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zhu, Anna; Zaharia, Oana-Patricia; Strom, Alexander; Bönhof, Gidon J.; Goletzke, Janina; Trenkamp, Sandra; Wagner, Robert; et al. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

X-Stream: A Flexible, Adaptive Video Transformer for Privacy-Preserving Video Stream Analytics - Dou, Feng; Wang, Lin; Chen, Shutong; Liu, Fangming (Proceedings of the IEEE International Conference on Computer Communications (INFOCOM))

Train Once Apply Anywhere: Effective Scheduling for Network Function Chains Running on FUMES - Blöcher, Marcel; Nedderhut, Nils; Chuprikov, Pavel; Khalili, Ramin; Eugster, Patrick; Wang, Lin (Proceedings of the IEEE International Conference on Computer Communications (INFOCOM))

𝜆Grapher: A Resource-Efficient Serverless System for GNN Serving through Graph Sharing - Hu, Haichuan; Liu, Fangming; Pei, Qiangyu; Yuan, Yongjie; Xu, Zichen; Wang, Lin (Proceedings of the ACM Web Conference (WWW))

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

Low-noise balanced homodyne detection with superconducting nanowire single-photon detectors - Protte, Maximilian; Schapeler, Timon; Sperling, Jan; Bartley, Tim (Optica Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) have been widely used to study the discrete nature of quantum states of light in the form of photon-counting experiments. We show that SNSPDs can also be used to study continuous variables of optical quantum states by performing homodyne detection at a bandwidth of 400 kHz. By measuring the interference of a continuous-wave field of a local oscillator with the field of the vacuum state using two SNSPDs, we show that the variance of the difference in count rates is linearly proportional to the photon flux of the local oscillator over almost five orders of magnitude. The resulting shot-noise clearance of (46.0 ± 1.1) dB is the highest reported clearance for a balanced optical homodyne detector, demonstrating their potential for measuring highly squeezed states in the continuous-wave regime. In addition, we measured a CMRR = 22.4 dB. From the joint click counting statistics, we also measure the phase-dependent quadrature of a weak coherent state to demonstrate our device’s functionality as a homodyne detector.

BelgienNet – une plateforme pour l’accès aux langues et cultures de la Belgique - Huybrechts, Yves; Karaca, Resul (Synergies Pays germanophones)

Teachers’ individual and collective efficacy in relation to their attitudes towards inclusion –Analyses from an international study comprising Canada, Germany & Switzerland. - Knickenberg, Margarita; Kullmann, Harry; Wüthrich, Sergej; Sahli Lozano, Caroline

Examining aspects of students’ current academic motivation in relation to peer interactions and social environment in the classroom using the Experience sampling method. - Knickenberg, Margarita; Zurbriggen, Carmen

Effects of peer interactions and the social environment on students’ current academic motivation in the classroom: An experience sampling study. - Knickenberg, Margarita; Zurbriggen, Carmen

Fast model-based calibration of multiple injections for a CI engine using nonlinear optimal control - Moretto, Giordano; Schnell, Nicolas; Frey, Jonathan; Karakaya, Yasin; Amstutz, Alois; Diehl, Moritz; Kasper, Tina; Onder, Christopher (Control Engineering Practice)

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research, in press)

Die Kriterien und Zusammensetzung der EU-Blacklist als Grundlage des Steueroasen-Abwehrgesetzes – Eine kritische Würdigung - Schön, Lena; Graßl, Benjamin; Giese, Henning (Steuer und Wirtschaft)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Was motiviert CoP-Mitglieder? Motivationale Bedingungsfaktoren für die Mitarbeit in Communities of Practice in der Lehrkräftebildung - Raneck-Kuhlmann, A.; Niemann, Jan; Buhl, Heike M.; Eickelmann, Birgit; Drossel, Kerstin (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Determinanten und Typen phasenübergreifenden Transfers in Communities of Practice der Lehrkräftebildung - Niemann, Jan; Raneck-Kuhlmann, A.; Eickelmann, Birgit; Drossel, Kerstin; Buhl, Heike M. (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Schulentwicklung, Chancengerechtigkeit und Digitalität – Verbindung zentraler Metathemen in einer zeitgemäßen Lehrkräftebildung - Schulze, J.; Eickelmann, Birgit; Drossel, Kerstin (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Photochemical Reaction Enabling the Engineering of Photonic Spin−Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society (JACS))

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)

Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

Equivalent-circuit model that quantitatively describes domain-wall conductivity in ferroelectric lithium - Zahn, Manuel; Beyreuther, Elke; Kiseleva, Iuliia; Lotfy, Ahmed Samir; McCluskey, Conor J.; Maguire, Jesi R.; Suna, Ahmet; Rüsing, Michael; Gregg, J. Marty; Eng, Lukas M. (Physical Review Applied)
Ferroelectric domain wall (DW) conductivity (DWC) can be attributed to two separate mechanisms: (a) the injection/ejection of charge carriers across the Schottky barrier formed at the (metal-)electrode-DW junction and (b) the transport of those charge carriers along the DW. Current-voltage (I-U) characteristics, recorded at variable temperatures from LiNbO3 (LNO) DWs, are clearly able to differentiate between these two contributions. Practically, they allow us to directly quantify the physical parameters relevant to the two mechanisms (a) and (b) mentioned above. These are, for example, the resistance of the DW, the saturation current, the ideality factor, and the Schottky barrier height of the electrode-DW junction. Furthermore, the activation energies needed to initiate the thermally activated electronic transport along the DWs can be extracted. In addition, we show that electronic transport along LNO DWs can be elegantly viewed and interpreted in an adapted semiconductor picture based on a double-diode, double-resistor equivalent-circuit model, the R2D2 model. Finally, our R2D2 model was checked for its universality by successfully fitting the I-U curves of not only z-cut LNO bulk DWs, but equally of z-cut thin-film LNO DWs, and of x-cut thin-film DWs as reported in literature.
Keywords: General Physics and Astronomy

Extended Dynamic Mode Decomposition: Sharp bounds on the sample efficiency - Philipp, Friedrich M.; Schaller, Manuel; Boshoff, Septimus; Peitz, Sebastian; Nüske, Feliks; Worthmann, Karl (arXiv:2402.02494)
We rigorously derive novel and sharp finite-data error bounds for highly sample-efficient Extended Dynamic Mode Decomposition (EDMD) for both i.i.d. and ergodic sampling. In particular, we show all results in a very general setting removing most of the typically imposed assumptions such that, among others, discrete- and continuous-time stochastic processes as well as nonlinear partial differential equations are contained in the considered system class. Besides showing an exponential rate for i.i.d. sampling, we prove, to the best of our knowledge, the first superlinear convergence rates for ergodic sampling of deterministic systems. We verify sharpness of the derived error bounds by conducting numerical simulations for highly-complex applications from molecular dynamics and chaotic flame propagation.

Historisches Lernen in einer ‚(Geschichts-)Kultur der Digitalität‘? - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Geschichtskulturen im digitalen Wandel?

Handbuch Poetikvorlesungen. Geschichte – Praktiken – Poetiken, hg. v. Gundela Hachmann, Julia Schöll u. Johanna Bohley, Berlin/Boston 2022 - Elit, Stefan (ZfdPh)

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

A note on the convergence of deterministic gradient sampling in nonsmooth optimization - Gebken, Bennet (Computational Optimization and Applications)
Abstract Approximation of subdifferentials is one of the main tasks when computing descent directions for nonsmooth optimization problems. In this article, we propose a bisection method for weakly lower semismooth functions which is able to compute new subgradients that improve a given approximation in case a direction with insufficient descent was computed. Combined with a recently proposed deterministic gradient sampling approach, this yields a deterministic and provably convergent way to approximate subdifferentials for computing descent directions.
Keywords: Applied Mathematics; Computational Mathematics; Control and Optimization

Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht.

Leibniz’s Influence on 19th Century Logic - Peckhaus, Volker (The Stanford Encyclopedia of Philosophy, first published Sep 4, 2009, substantive revision Feb 2, 2024)

Automatische Transkriptionssoftware – ein Erfahrungsbericht. - Schmidt, Rebecca (SozMethode)

Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Het verhaal van Vlaanderen. Analyse van het mediaformat en het geschiedverhaal - Huybrechts, Yves; Schmitz, Sabine (bmgn — Low Countries Historical Review)

Non-Fock ground states in the translation-invariant Nelson model revisited non-perturbatively - Hasler, David; Hinrichs, Benjamin; Siebert, Oliver (Journal of Functional Analysis)
Keywords: Analysis

Ruelle-Taylor resonaces of Anosov actions - Weich, Tobias; Guedes Bonthonneau, Yannick; Guillarmou, Colin; Hilgert, Joachim (J. Europ. Math. Soc.)

Quantum-Classical Correspondences for Locally Symmetric Spaces - Hilgert, Joachim

Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars

Phosphorhaltige Lasersinter-Materialien mit Flammschutzwirkung: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Schulz, Maurice

Sorgeprakiken der Online-Rechten – Jordan Petersons Therapeutik des ,Self-Authoring' - Degeling, Jasmin; Haffke, Maren (digital:gender - de:mapping affect. Eine spekulative Kartographie)

Fast Multiobjective Gradient Methods with Nesterov Acceleration via Inertial Gradient-Like Systems - Sonntag, Konstantin; Peitz, Sebastian (Journal of Optimization Theory and Applications)
We derive efficient algorithms to compute weakly Pareto optimal solutions for smooth, convex and unconstrained multiobjective optimization problems in general Hilbert spaces. To this end, we define a novel inertial gradient-like dynamical system in the multiobjective setting, which trajectories converge weakly to Pareto optimal solutions. Discretization of this system yields an inertial multiobjective algorithm which generates sequences that converge weakly to Pareto optimal solutions. We employ Nesterov acceleration to define an algorithm with an improved convergence rate compared to the plain multiobjective steepest descent method (Algorithm 1). A further improvement in terms of efficiency is achieved by avoiding the solution of a quadratic subproblem to compute a common step direction for all objective functions, which is usually required in first-order methods. Using a different discretization of our inertial gradient-like dynamical system, we obtain an accelerated multiobjective gradient method that does not require the solution of a subproblem in each step (Algorithm 2). While this algorithm does not converge in general, it yields good results on test problems while being faster than standard steepest descent.

A Descent Method for Nonsmooth Multiobjective Optimization in Hilbert Spaces - Sonntag, Konstantin; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Volkwein, Stefan (arXiv:2402.06376)
The efficient optimization method for locally Lipschitz continuous multiobjective optimization problems from [1] is extended from finite-dimensional problems to general Hilbert spaces. The method iteratively computes Pareto critical points, where in each iteration, an approximation of the subdifferential is computed in an efficient manner and then used to compute a common descent direction for all objective functions. To prove convergence, we present some new optimality results for nonsmooth multiobjective optimization problems in Hilbert spaces. Using these, we can show that every accumulation point of the sequence generated by our algorithm is Pareto critical under common assumptions. Computational efficiency for finding Pareto critical points is numerically demonstrated for multiobjective optimal control of an obstacle problem.